Performance effects of tubercle leading edge (TLE) on a cambered airfoil profile for vertical axis wind turbines (VAWTs) in steady wind - Lositaño, Ian Carlo M.
The Philippines is exploring and developing wind energy and other indigenous renewable energy resources. It has 76.6GW of harvestable wind energy capacity but only 427MW and 383MW of installed and dependable turbine capacities, respectively. These figures exclude the potential of vertical axis wind turbines (VAWTs), which has worldwide research initiatives currently reemerging with focus on performance improvement. In this study, the performance of a 5-kW capacity three-bladed H-rotor Darrieus VAWT with tubercle leading edge (TLE) as an added passive motion control on its cambered NACA 0025 blades was established using computational fluid dynamics (CFD). The TLE, based on whale flipper tubercles, has been shown to improve flow and performance of airfoils and horizontal axis wind turbines (HAWTs). A variety of computer-aided drawing (CAD) and computer-aided engineering (CAE) software were used to create the 2D and 3D geometries and meshes, run transient steady wind flow simulations and conduct post-processing analyses, k-w SST turbulence model was used to solve the pressure-based RANS equations. All 2D and 3D models were checked for cyclical and numerical convergence besides wall y+ acceptability. The 2D model served as transition prior the 3D simulations for performance benchmarking against reference studies and the 3D model, and establishing optimal spatio-temporal settings. Optimal y+ setting was determined to be 0.1 with the alternatives 1 and 30 failing to model the k-w SST turbulence model in blade-adjacent cells contrary to reference studies. Node density and time step parametric studies yielded the optimal values of 210 nodes and 1° azimuth time step equivalent. Both the baseline 2D and cambered 3D VAWT models showed agreement to the reference performance curves. Results showed the TLE to be detrimental to flow and performance of a cambered VAWT. Using torque, lift and drag data, the TLE VAWT was shown to deviate significantly against the cambered VAWT over one complete converged rotation, more specifically between the azimuth angles of 55° and 180°. TLE VAWT blades encounter reduced lift forces and increased drag forces, and from thereon lowered and reversal of torque values dipping up to -3.59Nm at 106° azimuth. Similar supporting observations were picked up from the z-vorticity and Q-criterion visualizations where the cambered VAWT was shown to have streamlined flow throughout the rotation while the TLE VAWT generated vortices the size of the blade chord at blade wakes between azimuthal positions of 106° and 180°. The z-vorticity plot further revealed flow separation at the blade crests creeping in at the blade trailing edge at 75° azimuth and reaching halfway through the blade chord length at 106° azimuth. Spanwise separation was restricted at blade crests. Flow degradation translates to poor performance. The net blade torque over one rotation of the TLE VAWT at the peak TSR generates only 9.28 W of blade power from the available wind power of 137.8W. Its power coefficient is 0.07 while that of the cambered VAWT is 0.30. The peak TSR of the TLE VAWT also shifted to A = 5 but without relevance.